Konstrusi Media Tentang Perempuan Pelaku Kejahatan Predator Seksual Anak : (Kajian Sosiologi Komunikasi dalam Perspektif Sosiologi) - Pribadi, Farid; Sadewo, FX Sri; Sukardani, Puspita Sari; Listayani, Refti Handini (Prodi Sosiologi Universitas Mataram, 2024)
This study seeks to reveal gender bias in the headline news of kompas.com concerning the case of a woman perpetrator of sexual crimes against 11 children in Jambi. The research utilizes Peter L. Berger's social construction theory, Erving Goffman's framing, and Pierre Bourdieu's symbolic violence. Employing Robert Entman's framing analysis model, the findings of this study uncover that the portrayal of women is divided into three constructs imbued with gender bias. Gender bias arises due to the practice of symbolic violence. First, the female perpetrator of sexual crimes is depicted as engaging in unseemly, reprehensible actions that contravene societal values and norms. Second, the woman's vital body becomes a newsworthy asset that is advantageous. Third, the news exhibits ambivalence; on one hand, it provides information on preventing sexual crimes, while on the other hand, it inadvertently offers a tutorial-like narrative on committing sexual offenses against children.